Examining The Effect of Travel Influencers on Travel Intention in Indonesia’s Super-Priority Tourism Destinations - Ivo Novitaningtyas; Ni Made Adelia Clarita; Gracia Alya Quina Akhmad; Nikken Nur Fanydia Ningsih (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2026)
The widespread adoption of social media has reshaped how travelers gather information and form travel intentions, particularly through the influence of travel influencers. As Indonesia promotes its super-priority tourism destinations, understanding this influence becomes increasingly relevant. This study examines the impact of travel influencers, modeled as a second-order construct with five dimensions: content expertise, inspiration, attractiveness, trustworthiness, and authenticity on travel intention. This study using a quantitative approach and data from 121 respondents collected via online survey. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that travel influencers significantly and positively influence travel intention to visit super-priority tourism destinations in Indonesia. Theoretically, this study contributes by offering a multidimensional conceptualization of travel influencers in tourism marketing research. Practically, it provides insight for tourism stakeholders and tourism marketers to collaborate with influencers who demonstrate credibility, inspiration, and authenticity in promoting super-priority tourism destinations in Indonesia.